PENANAMAN NILAI-NILAI KARAKTER PADA PENDIDIKAN ANAK USIA DINI BERDASARKAN PRESPEKTIF THOMAS LICKONA - Surya Iman Muhamad, - (2020)
This research is motivated by the inculcation of AUD character values, because by instilling character values from an early age children have awareness and commitment to apply virtue in everyday life. The purpose of this study is to examine Thomas Lickona's thoughts on character education and describe the problem formulation of how the concept of character education based on the second Thomas Lickona perspective is how to implement the concept of character education based on Thomas Lickona's perspective in the context of early childhood education. This research method using research literature studies. The method used in analyzing the data is Content Analysis. The data collection method used is the documentation method, using primary books, namely two books by Thomas Lickona, namely Educating for Character and Character Matters, while secondary data are journals and the results of other relevant research reports. by title. Based on the results of the study, it can be concluded that the concept of character education based on the Lickona perspective is a serious effort that involves three aspects in students including cognitive, affective and psychomotor to guide young people to be smart and have good and virtuous behavior. The implementation of character education based on Lickona's perspective in the context of early childhood in applying the concept begins with character teaching about respect and responsibility which can be the first step in understanding all the values of virtue.